The effect of double taxation treaties and territorial tax systems on foreign direct investment: Evidence for Spain - Ángela Castillo-Murciego; Julio López-Laborda (Economics: The Open-Access, Open-Assessment E-Journal, 2019)
The paper evaluates the effect of Double Taxation Treaties (DTTs) on Spain's inward and outward Foreign Direct Investment (FDI) for the period 1993-2013. Estimates produce positive and statistically significant coefficients. However, there are some differences between the inbound and outbound samples, the type of DTT and the group of developed and developing FDI partner countries. Moreover, interpretation of results differs depending on the fixed or random effects estimation technique used. The paper also analyses the effect on FDI of the rules agreed in DTTs and applied by the investors' residence country in order to correct international double taxation. The authors conclude that the tax saving derived from the application by Spain of the territorial system is positively related to investment from this country to abroad. However, the tax saving provided by the application by the partner countries of the territorial system does not have a significant effect on the investment of these countries into Spain.
http://dx.doi.org/10.7910/DVN/RTHLJ0
Keywords: F21; F23; F68; H25; H32; H87; 330; foreign direct investment; double taxation treaty; territorial tax system; Spain